y = (5x – 10)/2 ; 4x + 5 = - y

iii. y = (5x – 10)/2 ; 4x + 5 = - y


Sol. y = (5x – 10)/2

2y = 5x – 10

– 5x + 2y = – 10

Changing the sign,

5x – 2y = 10

Now, 4x + 5 = – y

 4x + y = – 5


D
=
5
-2
=
(5 × 1) – (4 × -2)
=
5 + 8
=
13


4
1








DX
=
10
-2
=
(10 × 1) – (-5 × -2)
=
10 – 10
=
0


-5
1








DY
=
5
10
=
(5 × -5) – (4 × 10)
=
-25  - 40
=
-65


4
-5








By Cramer's rule,

x
=
Dx
=
0
=
0


D

13




y
=
Dx
=
-65
=
-5


D

13





x = 0 and y = – 5 is the solution of given simultaneous equations.

No comments:

Post a Comment